An improved method of searching inferior parathyroid gland for the patients with papillary thyroid carcinoma based on a retrospective study - Yan, Shouyi; Lin, Lanqin; Zhao, Wenxin; Wang, Bo; Zhang, Liyong; Cai, Shaojun (Frontiers in Surgery, 2023)
Objective: More surgeons had known the importance of parathyroid gland (PG) in the thyroid surgery, but it was even more difficult to protect it. This study aimed at evaluating the effectiveness of the improved method of searching inferior parathyroid gland (IPG). Methods: 213 patients were enrolled and divided into test and control group according to different methods of searching IPG in the surgery. Consequently, we compared the surgical outcome parameters between the two groups, including the operative time, numbers of PG identifying (PG protection in situ, PG auto-transplantation and PG accidental removal), numbers of the total Lymph node (LN) and metastatic LN, parathyroid hormone (PTH), transient hypoparathyroidism, transient recurrent laryngeal nerve palsy, postoperative bleeding. Results: We identified 194 (194/196,98.98%) and 215 (215/230,93.48%) PG in the test group and control group respectively, and there was a significant difference (p = 0.005), and this result was due to IPG identification differences (96/98,97.96% VS 100/115,86.96%, p = 0.004). Meanwhile there was a lower ratio of IPG auto-transplantation in the test group compared with that in the control group (46.94% vs 64.35%, P=0.013). Serum PTH one day after the operation was 3.65±1.86 versus 2.96±1.64 (p = 0.043), but no difference at 6 months. Meanwhile there were no differences in metastatic LN and recurrent laryngeal nerve palsy between two groups. Conclusion: The improved method of searching IPG was simple, efficient, and safe, which was easy to be implemented for searching IPG and protecting it well.